Controlled Reactor with Increased Current-Limiting Capabilities - V. M. Prima; V. G. Repin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The problem is considered how to increase current-limiting capabilities of a controlled reactor with the help of compensation of contact magnetic flux of control windings by opposing flux of compensating windings. This compensation process takes place in the reactor magnetic circuit. The paper contains the results of experimental investigations using physical reactor model in the form of dependence characterictics family: dependence of reactor inductive impedance on changes in impressed voltage and current in its inducing windings. It has been shown that in steady-state mode of short-circuit reactor inductive impedance may exceed the impedance of its normal mode by 11-12-fold.